Effect of Foliar Application of Hydrogen Peroxide and Vitamin C on Some Enzymatic and Non Enzymatic Antioxidant of Two Cultivars of Hordeum vulgare L. Planted in Dry Farming Land - Wafik A. Al-Kaisy; Aso L. A. Al-Arkawazi (Journal of Madenat Alelem University College, 2017)
Field experimental was conducted during the season of growth (2014-2015) in one of the field Quratu sub district/ Khanakin/ Diyala province aiming to determine the influence of the interaction between both hydrogen peroxide and vitamin C on some enzymatic and non enzymatic antioxidant of two cultivars of barley ( Hordeum vulgare L. The results showed the increasing of hydrogen peroxide concentration from (zero to 10%) and also increase of vitamin C concentration from (zero to 150) mg/ L caused significance increase in non enzymatic antioxidant proline and vitamin C also increased to the function of enzymatic antioxidant CAT and POD for the both cultivars of barley especially at 100 mg/ L vitamin C and 10% hydrogen peroxidase compared with zero concentration (control).